Construction of circadian clock signature for tumor microenvironment in predicting survival of esophageal squamous cell carcinoma - Xiang, Yiping; Cui, Xuelian; Cui, Zhe (Frontiers in Immunology, 2026)
BackgroundEsophageal squamous cell carcinoma (ESCC) is a distinct subtype of esophageal cancer (EC). Research indicates that circadian clock genes (CCGs) in human ESCC are dysregulated. However, the significance of CCGs in ESCC prognosis remains ambiguous. This study sought to establish a complete signature of ESCC-specific differentially expressed CCGs (DE-CCGs) associated with prognosis, tumor growth, and immunological infiltration.MethodsDifferentially expressed genes (DEGs) between normal and ESCC samples in TCGA database and the GSE23400 dataset were intersected with CCGs to obtain DE-CCGs. The prognosis-related DE-CCGs were discerned to develop a risk model using univariate Cox regression and LASSO regression analyses in TCGA-ESCC. The accuracy of the model was validated using risk and overall survival profiles.ResultsSeven DE-CCGs (CST3, C1QBP, TTF2, EGFR, CDKN2A, PFAS, TRRAP) were identified in TCGA-ESCC, which were correlated with unfavorable ESCC prognosis. The immune infiltration analysis revealed that High-risk ESCC patients displayed enhanced tumor infiltration. And the combination of CST3 and PD-L1 expression may serve as a potential marker for predicting prognosis of ESCC patients. Moreover, in Vitro experimental models, CST3 expression was markedly elevated in tumor cells and associated with ESCC growth.ConclusionsThis research illustrated the prognostic significance of seven DE-CCGs for ESCC patients based on tumor progression and immune infiltration. And the CST3 may serve as an independent prognostic biomarker and a potential therapeutic target for ESCC.